Smoking Status Trends between Primary Total Hip Arthroplasty Patients and the General Population from 2012 to 2021 - Nwakoby, Ekenedilichukwu; Bieganowski, Thomas; Singh, Vivek; Anil, Utkarsh; Schwarzkopf, Ran; Lajam, Claudette M. (The Journal of Hip Surgery, 2023)
Smoking is associated with an increased risk of complications, higher opioid use, and mortality following primary elective total hip arthroplasty (THA). Interventions for smoking cessation have been enhanced since value-based care was initiated in 2013. It remains unclear whether surgical optimization has influenced the proportion of smokers undergoing THA over time. Our study examines trends in the yearly proportions of smokers for primary elective THA versus patients having annual physical examinations (APEs). We retrospectively reviewed all patients of 18 years of age or older who underwent primary elective THA and those who had an APE at our institution between January 2012 and December 2021. The electronic medical record was queried for baseline demographics and documented smoking status. Linear regression analysis was used to determine trend significance. In total, 12,524 primary THA patients were matched in a 1:5 ratio to 62,630 APE patients using nearest-neighbor matching. Our analysis demonstrated significantly higher proportions of documented current and former smokers within the THA group at each time point compared with the APE group. The rate of current smokers undergoing THA demonstrated a downward trend that was not significant. There was a significant upward trend in documented current smokers presenting for an APE. Although there has been a decrease in active smokers undergoing THA at our institution over the past decade, this trend is not significant. Therefore, it remains unclear whether smoking cessation interventions have influenced patients undergoing primary THA. Continued vigilance in smoking cessation strategies is warranted, and improved documentation of smoking status may enhance our current understanding of whether optimization efforts are successful.Level III Evidence Retrospective cohort study.
Keywords: smoking; total hip arthroplasty; value-based care; trends; optimization